Challenges and Opportunities in Smart Antenna - Kiran, W. S. (IRO Journal on Sustainable Wireless Systems, 2022)
The ever-increasing demand for larger bandwidth with seamless and fast data access for commuters resulted in developing new challenges for wireless service providers. With the increasing network mobility, the communication channel based characteristics between base stations and mobile users are changing rapidly. To meet these challenges, smart antennas have become an essential component in the emerging wireless systems. The increasing requirement for increasing stable network performance and reducing electromagnetic pollution has strengthened smart antenna adoption. The primary objective of this research study is to highlight current research works in the area of smart antennas by evaluating the key technologies, service strategies, solutions and its importance in terms of 5G including network coverage enhancement, data speed, and Quality of Service (QoS).
Keywords: 5G Smart Antennas; MIMO; Wi-Fi; Wi-MAX; Cellular Systems